2016
DOI: 10.1002/ajcp.12097
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the Psychosocial Well‐being of Military Members and Their Partners: The Importance of Community and Relationship Provisions

Abstract: Evidence of the impact of communities has been documented for a variety of individual and relational outcomes, including mental and physical health as well as the quality of romantic and parent-child relationships. The military represents a rather unique work context; in that, it is generally considered a lifestyle with a distinct culture and community. Yet, military families are also members of their broader, comprehensive community. Drawing from the social organizational theory of action and change (SOC) (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
(35 reference statements)
1
27
2
Order By: Relevance
“…It seems that for civilians, having connections may impact the sentiments they attach to military life as a whole, but it may play a limited role in how they actually handle the demands of military life. While on the surface this is counter to expectations, some research suggests that for civilian spouses their broader community connections, rather than their military community connections, are more influential (O'Neal et al., ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It seems that for civilians, having connections may impact the sentiments they attach to military life as a whole, but it may play a limited role in how they actually handle the demands of military life. While on the surface this is counter to expectations, some research suggests that for civilian spouses their broader community connections, rather than their military community connections, are more influential (O'Neal et al., ).…”
Section: Discussionmentioning
confidence: 91%
“…Community connections among military members and their families provide opportunities to connect with others living the military life (e.g., fellow service members, civilian spouses). These connections can provide resources and support needed to cope with general life stressors (O'Neal, Mancini, & DeGraff, ). In the current study, we examine how community connections help military members and their spouses cope with the stress of military culture and its demands, and how this coping specific to military‐related situations is reflected in personal and family well‐being (i.e., mental health, life satisfaction, family functioning).…”
Section: Theoretical Perspectives On Contexts Processes and Well‐beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these experiences and more, community connections may be particularly vital for military families as communities represent an extra‐familial resource and source of support. The role of community is evident in research with military samples, which has found that community connections may deter negative effects of stressful transitions and foster positive individual and family functioning (Bowen et al., ; O'Neal, Mancini, et al., ). For example, spouses of military members with more comprehensive informal networks and formal community systems report more positive adaptation when faced with military‐related separations or transitions (Davis, Ward, & Storm, ; Orthner & Rose, ).…”
Section: Introductionmentioning
confidence: 99%
“…() argued that parents in resilient families often demonstrate the ability to mobilize community resources and use coping strategies that allow for effective stress management while maintaining balance within the family. Engagement in one's community, combined with a strong sense of community, is linked with adult well‐being (Bruhn, ; O'Neal, Mancini et al., ;) and an increased ability of family members to cope with stressors and demonstrate resilience (Bowen et al., ). Walsh () has discussed key processes in family resilience, and includes in her framework an element she terms “connectedness,” which reflects processes of mutual support, collaboration, and commitment, all essential aspects of dealing with adversity at the individual and the family level.…”
Section: Introductionmentioning
confidence: 99%